2010
DOI: 10.1111/j.1750-3841.2010.01668.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Fluidized Bed System for Wheat Grain Disinfection

Abstract: Durum wheat grain from the field is naturally contaminated with bacteria, yeast, and mold. The reduction in aerobic plate count (APC) and yeast and mold count (YMC) is often necessary before processing wheat. Gaseous ozone, ozonated water, and acetic acid solution are nontraditional antimicrobial agents for grains and are safe for humans and the environment. Better disinfection may be possible by applying antimicrobial agents to grain in a fluidized state. Fluidization increases the exposure of grain surfaces,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…Reductions in yeast and mold similar to those obtained in this study were reported by Dhillon et al (2010) using a fluidized bed system, acetic acid, and ozonated water. They reported that a combination of gaseous ozone (6 ppm), acetic acid (0.5%), and ozonated water (26 ppm) was the most effective in reducing yeast and mold counts (3.3 log CFU/g).…”
Section: Resultssupporting
confidence: 88%
“…Reductions in yeast and mold similar to those obtained in this study were reported by Dhillon et al (2010) using a fluidized bed system, acetic acid, and ozonated water. They reported that a combination of gaseous ozone (6 ppm), acetic acid (0.5%), and ozonated water (26 ppm) was the most effective in reducing yeast and mold counts (3.3 log CFU/g).…”
Section: Resultssupporting
confidence: 88%
“…After washing wheat kernels with this solution for 3 min, the APC and yeast/mold counts were reduced by 3.20 and 4.10 log CFU/g, respectively. In a follow-up study, Dhillon, Wiesenborn, Dhillon, and Wolf-Hall (2010) utilized a fluidized bed system to apply a combination of gaseous ozone (6 ppm), acetic acid (0.5%), and ozonated water (26 ppm) to reduce the microbial load of durum wheat grain. A reduction in APC of 1.70 and 3.30 log CFU/g for yeast/mold counts was noted after the application of this treatment.…”
Section: Inactivation Of Wheat Natural Microbiota By Tempering Withmentioning
confidence: 99%
“…Ozonated water was also reported to be effective for microbial inactivation of a range of foods, including grains, and can be an alternative to chlorinated water before milling. Dhillon, Wiesenborn, Dhillon, and Wolf‐Hall () found that although washing durum wheat grains with ozonated water did not show high antimicrobial efficacy when used alone, it was effective in combination with acetic acid. Similarly, a combination of gaseous ozone, acetic acid, and ozonated water, using a fluidized bed system, was the most effective in reducing microbial counts on durum wheat in another study (Dhillon et al., ).…”
Section: Current and Potential Techniques For Control Of Microbial Spmentioning
confidence: 99%